Richness and diversity of ants (Hymenoptera: Formicidae) according to land use in two agroforestry landscapes of Colombia - Marquez-Peña, Johana (2023)
Introduction: Ants fulfill important ecological functions in many ecosystems and are highly sensitive to changes in land use. However, the response to these changes is poorly documented, at large spatial scales and in different land uses, in poorly studied ecosystems such as the Serranía del Perijá. Objective: To analyze the richness, diversity, and composition of ant communities in four land uses of two agroforestry landscapes of the Serranía del Perijá, Cesar, Colombia. Methods: Two sampling windows of 4 × 4 km were delimited in two agroforestry landscapes (compensation and non-compensation). In each window and landscape four land uses were chosen: forests, coffee agroforestry systems, natural regeneration and pastures, in which two trapping methods were applied: Pitfall traps and Winkler bags. Six environmental variables were measured: canopy cover, leaf litter height, bulk density, temperature, humidity and soil hardness. The sampling effort was 384 Pitfall traps and 192 m2 of leaf litter extraction. The fieldwork was conducted between February and March 2021. Results: Ants showed high sensitivity to changes in land use. Species diversity and richness decreased in land uses with less natural vegetation cover, such as pastures; while forests, in both landscapes, retained the highest species richness. Canopy cover and leaf litter availability were the environmental parameters that favored the diversity and richness of ant communities in all land uses. No differences were found between the ant richness and diversity of the two landscapes studied. Conclusions: Ants respond to changes in land use, particularly to vegetation cover. Our hypothesis was confirmed since land uses with high vegetation cover were the habitats with the greatest richness and diversity of ants. Environmental heterogeneity, a product of the dynamics of landscape transformation, is an element that should be considered in future research.